2023
DOI: 10.1093/nar/gkac1270
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-associated type V proteins as a tool for controlling mRNA stability inS. cerevisiaesynthetic gene circuits

Abstract: Type V-A CRISPR-(d)Cas system has been used in multiplex genome editing and transcription regulation in both eukaryotes and prokaryotes. However, mRNA degradation through the endonuclease activity of Cas12a has never been studied. In this work, we present an efficient and powerful tool to induce mRNA degradation in the yeast Saccharomyces cerevisiae via the catalytic activity of (d)Cas12a on pre-crRNA structure. Our results point out that dFnCas12a, (d)LbCas12a, denAsCas12a and two variants (which carry either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Since this output signal is visible to the naked eye, the usage of laccase together with ABTS can speed up considerably the screening for strains containing a working synthetic gene circuit. We have already used TtLcc1 as a reporter to evaluate the efficiency of mRNA degradation caused by CRISPR type V proteins [ 17 ]. Here, we harnessed TtLcc1 to evaluate gene editing efficiency in a knockout circuit (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this output signal is visible to the naked eye, the usage of laccase together with ABTS can speed up considerably the screening for strains containing a working synthetic gene circuit. We have already used TtLcc1 as a reporter to evaluate the efficiency of mRNA degradation caused by CRISPR type V proteins [ 17 ]. Here, we harnessed TtLcc1 to evaluate gene editing efficiency in a knockout circuit (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCR products and the cut-open vector were added into 15 μL Gibson isothermal mixture to obtain a final volume of 20 μL. These 20 μL were placed at 50 °C for 1 h. 5 μL were used to transform DH5α (Life Technology––18263–012) Escherichia coli cells (30 s heat shock at 42 °C) [ 15 ]. New plasmids were checked via Sanger-sequencing at Genewiz Inc., Suzhou (China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that some Cas9s are able to target RNA in a protospacer adjacent motif (PAM)‐independent way (Strutt et al., 2018 ; Zhang et al., 2022 ). Other endonucleases, such as Cas6f (class 1, type I; formerly known as Csy4) or Cas12a, have been used to cleave a specific mRNA and induce its degradation (Qi et al., 2012 ; Yu & Marchisio, 2023 ), although not in a programmable way (i.e. through genetic modification of the target).…”
Section: Rna Silencingmentioning
confidence: 99%
“…By leveraging our deep understanding of yeast biology and genetic resources, we have previously implemented a wide variety of biological circuits, especially biosensors, that were based on transcription/translation regulatory mechanisms in budding yeast [ 6 ]. The yeast S. cerevisiae represents a commonly used chassis for synthetic gene circuits because it is a unicellular eukaryotic organism whose genome is well annotated and relatively easy to manipulate by using homologous recombination [ 7 ].…”
Section: Introductionmentioning
confidence: 99%